Scared Sacred: How the Horrifying Story of Joseph Smith's Polygamy Can Help Save Us - Carter, Stephen (Dialogue, 2016)
The article presents the author's views on the polygamy of Mormon Church founder Joseph Smith. He states that Smith's polygamy is disturbing, however, he was defended by the church arguing that an angel forced him into it. The story of Abraham and Isaac is discussed as well as how Biblical stories can be against God's teachings. Also explored are child abuse and theology of Smith.